Estudio de mercado de insumos agrícolas para posicionamiento y crecimiento de una empresa con fines de rentabilidad en la zona del cantón Buena Fe - Carriel Herrera, Jennifer Andrea (2018)
In our country the agricultural sector has become one of the most important sources of income in the Ecuadorian economy due to its great production, we see the need of agricultural inputs for land treatment and crop improvement , increasing profitability in production. This research aims to develop a market study of agricultural inputs, with emphasis on crops (African palm, pineapple, ginger, banana, cocoa and maize), looking for niche markets for the positioning of a company in the canton area Good faith, selecting the best selling products and their degree of acceptance. The methodology applied in the research allowed to obtain the primary information through the use of surveys and interviews applied to the farmers (consumers) and offerers (vendors) with questions related to the objectives raised. The results showed that there is an excess of demand that is unsatisfied, since the companies that dispense agrochemicals are not enough or specific for the use of the different crops in the area. The economic analysis showed that the volumes of sales of the inputs fluctuated between 28,588.00 and 34,740.00 being the agricultural "Vásquez" which highest degree of acceptance, followed by the Agroservicios "Ubilla" with 34,153.90 having a difference in the sales of 1.7%; With a profitability of 31% while the Agro "Lara" showed a 33% in such a way that the other agrochemical were observed volumes important in the sales but did not reach their acceptance having with them a low profitability. Key words: Market research, agricultural inputs, demand, supply, unmet demand, profitability.